Oral and Dental Health Knowledge, Attitude and Performance of Dental Students of Kerman University of Medical Sciences - Razieh Hoseinifar; Niloofar Shadman; Romina Hajizadeh (Isfahan University of Medical Sciences, 2023)
Oral and dental health is a crucial aspectof overall healthand has a great impact on the quality of life. The aim of this study was to evaluate theknowledge, attitude and performance of dental students of Kerman University of Medical Sciences in the field of oral and dental health.Materials & Methods:In this cross-sectional study, a questionnaire was completed by 240 dental students of Kerman University of Medical Sciences and information about age, gender, years of education, parents' education, knowledge, attitude and performance of dentalstudents in the field of oral and dental health were collected. To analyze the data, Pearson correlation coefficient and linear regression step by step method using Baron and Kenny test and Chi-square test. The level of significance was set at a p value < 0.05.Results:48% of students had high knowledge and 42% had a positive attitude towards oral and dental health. There was no significant relationship between the variables of age and type of entry into dentistry and the variables of attitude, knowledge and practice (p value > 0.05). Women and those whose parents were dentists had significantly better oral and dental health performance. There was a significant relationship between knowledge and performance and between attitude and knowledge (p value < 0.05).Conclusion:The status of students' oral and dental health knowledge, attitude and performance are moderate and It is essential to develop effective programs to improve these variables to enhancethe individual and professional performance of students in this field